Cover Image, Volume 3, Issue 1. Issue 1 (20th February 2020) - Unknown
Abstract : CRYSTALLIZATION MORPHOLOGY AND FORMATION MECHANISM OF PA1012‐ MB PTMO COPOLYMERS In their work reported in article e10100, Xia Dong and colleagues discussed the crystallization morphology and corresponding formation mechanism of a novel series PA1012‐ mb ‐PTMO copolymers within thin/ultrathin films. The researchers found that the PTMO segments and the film thickness were the key factors in determining the crystalline structure and morphology. The cover image shows AFM height and TEM images of PA1012‐ mb ‐PTMO copolymers thin and ultra‐thin films with varied thickness cooled from the melt at 10 °C/min. (DOI: 10.1002/PCR2.10100 ) Abstract : CRYSTALLIZATION MORPHOLOGY AND FORMATION MECHANISM OF PA1012‐ MB PTMO COPOLYMERS In their work reported in article e10100, Xia Dong and colleagues discussed the crystallization morphology and corresponding formation mechanism of a novel series PA1012‐ mb ‐PTMO copolymers within thin/ultrathin films. The researchers found that the PTMO segments and the film thickness were the key factors in determining the crystalline structure and morphology. The cover image shows AFM height and TEM images of PA1012‐ mb ‐PTMO copolymers thin and ultra‐thin films with varied thickness cooled from the melt at 10 °C/min. (DOI: 10.1002/PCR2.10100 )